BANTUAN KEUANGAN ANTAR PEMERINTAHAN DI INDONESIA - Suyanto, (Pendidikan Ekonomi, 2010)
This essay aims to theoretically examine intergovernmental transfer from central government to local government, especially to municipality and city. It focuses on government considerations of transfer, types of transfer, modes for determining transfer, and criteria to determine effective transfer. It finds that a country chooses a type of transfer based on its typical purposes. Indonesia only recognizes two types of transfers; specific grants and block grants. The basis for determining fund through intergovernmental fiscal transfer can be in form of; 1) based on fixed percentage from income originating from central government; 2) following an ad hoc basis; and 3) based on formula mechanism. This third variant is found widely around the world. Indonesia uses percentage and formula method. There are some requirements for effective transfer system. The first demands that local government must fund its own expenses for public services using its own financial resources. The second system uses the formula  discouraging the occurrence of financial deficit. The third states that the formula of financial transfer should be equal with the need of local fiscal and it should be in reverse comparison with the capacity of local fiscal. The fourth stresses the transparency and stability.